Dignity and physical self determination as basis of patient status - Gómez Sánchez, Yolanda (Acta Bioethica, 2011)
This study reflects on patient status. Both States Laws and international and supranational laws have respond to changes operated in health sciences, incorporating specific norms related to human rights. Dignity and individual freedom concepts are analyzed as necessary basis for patient status and personal freedom manifested in the field of biomedicine is defended by a new right: the right to physical self determination, which defines the field to improve decision making faculties, protected by law and that allows the person to decide, choose and select what to do or not to do with respect to questions and situations that affect his/her physical reality, his/her corporeity.